PEMANFAATAN KOTORAN SAPI SEBAGAI SUMBER ENERGI PENGGANTI BAHAN BAKAR MINYAK - Yorinda Buyang; Ivylentine D. Palittin; Richard S. Waremra (Universitas Bengkulu, 2019)
Petroleum scarcity has been a yearly problem facing Indonesian society during the last three decades. The program aimed at helping Indonesian society fulfilling their daily needs of energy by creating biogas as a renewable source of energy. In doing so, we employed a demonstrative method. The research flows are follows: 1) providing all the requirements needed ( 50 Kg of wet cow manure, yeast, pipes, faucets, hose, and gas stove respectively); 2) providing an instruction of the importances of biogas for daily life and the procedures of creating biogas for 50 participants in Amun Kay and Hidup Baru village ; 3) practicing directly of biogas production; 4) asking the participants to practicing for their own. The findings were: 1) producing biogas as a substitute for kerosene as much 4,16 m3(2.6 L kerosene) could be used as substitute energy of kerosene for cooking for 3-4 days for 4-5 people; 2) producing 15 Kg dry organic fertilizer.